Race and ethnicity - Heidi Safia Mirza; Ross Warwick (Institute for Fiscal Studies (IFS), 2022)
This chapter considers inequalities across ethnic groups in the United Kingdom and finds that there is no single story of advantage or disadvantage. Ethnic inequalities are complex and characterised simultaneously by continuity rooted in historical origins and conditions, and rapid change fuelled by new and changing populations and opportunities. Continuity and change are also reflected in very different patterns of inequality across (and within) minority groups, generations, and outcomes. The populations of the UK's diverse minority ethnic groups today arrived at different times, from different countries and cultures, and equipped with different levels of educational and human capital. Perhaps unsurprisingly, these groups now show varied fortunes. Some are characterised by high levels of average qualifications, income and wealth, while others are persistently disadvantaged, faced with elevated levels of poverty and unemployment. Alongside different levels in outcomes are varied trajectories, both within and across generations. Within groups, there are less-explored, intersectional contours of difference, along the lines of gender, geography and class. Research and policy must acknowledge this diversity and complexity in order to inform effective policy prescriptions going forwards.
Keywords: 330; Poverty; inequality and social mobility; Race; Inequality